Parents' Attention Relationship with Student Learning Motivation in The Process Education Learning - Muhammad Irkham; Galih Istiningsih; Puji Rahmawati (Prosiding University Research Colloquium, 2022)
This study aims to determine the relationship between parents with student learning motivation in the learning process in class IV, V and VI SDN Tlogorejo, Grabag District, Magelang Regency. This study uses a quantitative method with a type of correlational research. The sampling technique used is random sampling, samples are taken randomly. The data collection technique used in this study is to use a questionnaire. The results showed that there was a positive relationship between parents' attention and student learning motivation in learning. The result were obtained from the correlation coefficient of 0,407 > from rtable 0,273 with a significance level of 0.002<0,05 with a correlation coefficient at intervals of 0,410-0.600 Which means having a moderate level of relationship, with the value of R Square 0,165 which means the parent’s attention variables have an effect of 16,5% of student learning motivation, while 83,5% are influenced by other factors.